Lutetium, scandium and neodymium co-doped yttrium aluminum garnet crystal as well as growth method and application thereof

By co-doping Lu3+ and Sc3+ in Nd:YAG crystals, the saturation flux and energy storage capacity of Nd:YAG crystals are improved, and the problems of low saturation flux and mechanical properties of Nd:YAG crystals in the prior art are solved, and the problems of low saturation flux and reduced mechanical properties of Nd:YAG crystals are realized. It has efficient laser output and improved mechanical performance, and is suitable for heavy frequency large energy lasers.

CN119121402APending Publication Date: 2024-12-13SHANGHAI INST OF OPTICS & FINE MECHANICS CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411078927.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-07
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing Nd:YAG crystals are low in saturation flux and poor in high-energy laser gain medium, and the mechanical properties and thermal conductivity will be reduced during doping, which cannot meet the high thermal conductivity, excellent mechanical properties and high quality at the same time. Comprehensive indicators such as laser efficiency.

Method used

Co-doped Lu3+ and Sc3+ in Nd:YAG crystals, the saturation flux is increased through Sc3+, and the lattice distortion caused by Lu3+ equilibrium doping increases the effective coagulation coefficient of the activated ion Nd3+, increases the disorder of the crystal field, and reduces emission cross-section, thereby improving saturation flux and energy storage capacity, while suppressing the generation of dual-wavelength lasers.

Benefits of technology

It effectively improves the saturation flux of Nd:YAG crystal by about 1 to 2 times, optimizes the luminescence uniformity and mechanical properties, enhances the energy storage capacity of the crystal, and is suitable for heavy frequency large energy lasers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121402A_ABST
    Figure CN119121402A_ABST
Patent Text Reader

Abstract

The chemical composition general formula of the lutetium, scandium and neodymium co-doped yttrium aluminum garnet crystal is (NdxY1-x-yLuy) 3 (Al1-zScz) 2Al3O12, x is larger than or equal to 0.002 and smaller than or equal to 0.013, y is larger than or equal to 0.005 and smaller than or equal to 0.05, and z is larger than or equal to 0.1 and smaller than or equal to 0.2. The saturation flux of the Nd: YAG is increased by about 1-2 times, and other spectral characteristics, chemical stability, mechanical performance, laser performance and other characteristics of the Nd: YAG are not obviously changed while the luminescence uniformity of the Nd: YAG crystal is optimized. The lutetium-scandium co-doped neodymium-doped yttrium aluminum garnet crystal obtained based on the method can effectively improve the energy storage characteristic, and has important application in high-energy laser.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of laser crystal materials, and in particular to a lutetium-scandium-neodymium co-doped yttrium aluminum garnet crystal and a growth method and application thereof. Background Art

[0002] The research and development of gain media for high-energy pulsed lasers with high repetition rates is one of the main development directions of solid-state lasers. Using appropriate gain media, high-energy pulsed lasers with pulse widths of tens to hundreds of joules, tens of hertz, and nanoseconds can be generated. This type of laser has important applications in industrial processing, laser weapons, shock-hardened medical treatment, large scientific equipment, and other fields.

[0003] At present, high-energy pulse lasers mainly use neodymium glass as the gain medium. However, due to the limitation of thermal conductivity, neodymium glass cannot produce high-energy pulse lasers with high repetition rate. Neodymium-doped yttrium aluminum garnet (Nd:YAG) crystals have excellent physical and chemical properties, high thermal conductivity, high mechanical strength, not easy to damage, and high reliability. Using Nd:YAG crystals as gain media to generate Joule-level repetition rate lasers at room temperature can produce 12J, 10Hz pulse lasers (T.Liu, Z.Sui, L.Chen, Z.Li, Q.Liu, M.Gong, and X.Fu, 12J, 10Hz diode-pumped Nd:YAG distributed active mirror amplifier chain with ASE suppression, Opt. Express, 2017, 25, 18, 21981-21992). However, due to the low saturation flux of Nd:YAG crystals (0.66J / cm 2 ), resulting in the Nd:YAG crystal unit area can not obtain higher pulse energy, the energy storage capacity is poor. 3+ Ion and Y 3+ The ionic radius is very different, resulting in Nd 3+ The segregation coefficient of ions in YAG crystals is small (0.2) and the uniformity is poor.

[0004] In recent years, some methods of regulating the luminescence spectrum of laser crystals by co-doping trivalent non-luminescent elements have been reported. For example, D. Li et al. published in Journal of Alloys and Compounds that 10% Gd was doped into YAP crystals. 3+, which can improve the disorder of the crystal (D.Li, Q.Liu, P.Zhang, H.Zhou, Siqi Zhu, Y.Zhang, Z.Li, H.Yin, Z.Chen, Y.Hang, Crystal growth, optical properties and laser performance of new mixed Nd 3+ doped Gd 0.1 Y 0.9 AlO3 crystal, J.Alloys Compd., 2019, 789, 664-669). For Nd:YAG crystals, some cases of trivalent rare earth element co-doping have also been published, such as J.Di et al. reported Nd:Lu 1.5 Y 1.5 Al5O 12 Crystal (J.Di, 1.5 Y 1.5 Al5O 12 laserLaser Phys.Lett.2013,10,095801), C.Feng et al. reported Nd:Y3ScAl4O 12 crystals, the crystal field disorder of these crystals is enhanced compared to Nd:YAG (C.Feng, H.Zhang, Q.Wang, J.Fang, Dual-wavelengthsynchronously mode-locked laser of a Nd:Y3ScAl4O 12 disordered crystal LaserPhys.Lett.2017,14,045804).

[0005] Although the above-mentioned mixed crystals have the characteristics of enhanced disorder, they are not suitable as high-energy laser gain media, and many negative phenomena will occur in the process of increasing disorder. 3+ Capable of generating laser light at around 1.06 μm, corresponding to the energy level 4 F 3 / 2 → 4 I 11 / 2 The transition, 4 F 3 / 2 and 4 I 11 / 2The energy level is split into 2 and 6 sub-energy levels respectively under the action of the crystal field, so a total of 12 transition lines will be generated in the energy level transition. In the crystal with high disorder of neodymium doping, it is very easy to emit dual-wavelength laser output, which reduces the light-to-light conversion efficiency, such as the previously mentioned Nd:Y3ScAl4O 12 In addition, previous studies on scandium-containing yttrium aluminum garnet have focused on two main matrices: Y3ScAl4O 12 and Y3Sc2Al3O 12 Both of these crystals do not meet the requirements of being a gain medium for a high-energy laser system with a high repetition rate. They operate as dual-wavelength lasers in the laser system. The effects of doping at different lattice sites on the disorder of the crystal are different. In garnet crystals, even if a large proportion of doping occurs at the dodecahedral lattice site, the disorder of the crystal will not be reduced much, such as the Nd:Lu mentioned earlier. 1.5 Y 1.5 Al5O 12 The crystal still has a low saturation flux. In addition, during the disorder doping process, mechanical properties such as thermal conductivity, fracture toughness and Young's modulus will be significantly reduced, which will deteriorate the overall performance of the crystal.

[0006] Garnets containing YAG components disclosed in existing patents and literature cannot meet the requirements of high-frequency high-energy lasers, and cannot simultaneously meet comprehensive indicators such as high thermal conductivity, excellent mechanical properties, suitable saturation flux and high laser efficiency. Summary of the invention

[0007] In view of the comprehensive index requirements of repetitive high-energy lasers for gain media, the purpose of the present invention is to provide a lutetium-scandium-neodymium co-doped yttrium aluminum garnet crystal that can effectively improve the saturation flux without producing significant negative effects on the physical, chemical and growth properties of the crystal, as well as a high-energy laser based on the crystal.

[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0009] The present invention provides a lutetium-scandium-neodymium co-doped yttrium aluminum garnet crystal, characterized in that: the chemical composition formula of the crystal is (Nd x Y 1-x-y Lu y )3(Al 1-z Sc z )2Al3O 12 , 0.002≤x≤0.013, 0.005≤y≤0.05, 0.1≤z≤0.2.

[0010] Co-doping Lu in Nd:YAG Crystal 3+ and Sc 3+ . Lu that does not shine3+ and Sc 3+ , occupying different grid positions. 3 + Doping can effectively improve the saturation flux of Nd:YAG crystals. 3+ Doping can balance Sc 3+ and Nd 3+ The lattice distortion caused by doping reduces the cracking of crystals during growth and processing. 3+ It can increase the unit cell volume and incorporate Lu 3+ The radius compensation effect can increase the activation ion Nd 3+ The effective segregation coefficient of the crystal is increased, thereby improving the uniformity of the crystal's luminescence, which is conducive to the large-scale growth of Lutetium-Sc co-doped Nd:YAG crystals. The co-doped Lutetium-Sc ions increase the disorder of the crystal field, reduce the emission cross section of the Nd:YAG crystal, and make the Nd 3+ The saturation flux of ions increases by 1 to 2 times, improving the energy storage capacity of the crystal.

[0011] Sc 3+ There is a certain limit on the doping amount, Sc 3+ Too high a content will cause the laser system to operate at dual wavelengths. 3+ If the content is too low, the crystal saturation flux will not increase significantly. After a series of experiments, Sc 3+ The content of 10% to 20% of the octahedral lattice is more appropriate, and the saturation flux increases with the increase of scandium concentration. At this doping concentration, the saturation flux increases significantly, and dual-wavelength lasers will not appear. The laser wavelength is 1064nm. 3+ The crystal has a certain tendency to crack. It has been verified by experiments that adding a small amount of Lu 3+ This tendency can be effectively suppressed. 3+ It balances the lattice distortion caused by doping, reduces the cracking of crystals during growth and processing, and is conducive to the large-size growth of Nd:YAG crystals.

[0012] Furthermore, the crystal is grown by a melt method.

[0013] The invention also provides a use of lutetium-scandium-neodymium co-doped yttrium aluminum garnet crystal in solid-state lasers. Furthermore, the solid-state laser can be widely used in high-energy laser fields such as repetition rate high-energy lasers, laser shock strengthening, petawatt laser pump sources, laser fusion ignition devices, laser weapons, etc.

[0014] Compared with the prior art, the excellent effects of the present invention are:

[0015] The present invention co-doped lutetium-scandium ions into Nd:YAG crystals to increase the disorder of the crystal field and increase the crystal saturation flux by about 1 to 2 times, while increasing the Nd3+ The effective ion segregation optimizes the luminescence uniformity of the Nd:YAG crystal, while not causing significant changes in other spectral characteristics, chemical stability, mechanical properties and laser properties of Nd:YAG, and has excellent comprehensive properties. The lutetium-scandium co-doped neodymium-doped yttrium aluminum garnet crystal of the present invention can effectively improve the energy storage characteristics and has important applications in high-energy lasers. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a schematic diagram for testing the laser slope;

[0017] Among them, 1-LD pump source; 2-focusing coupling system; 3-input mirror; 4-tested crystal; 5-output mirror; 6-output laser;

[0018] Figure 2 Nd 0.03 Lu 0.06 Y 2.91 Sc 0.2 Al 4.8 O 12 The thermal conductivity of the crystal measured changes with temperature;

[0019] Figure 3 Nd 0.03 Lu 0.06 Y 2.91 Sc 0.2 Al 4.8 O 12 Mechanical properties test report of crystal;

[0020] Figure 4 Nd 0.03 Lu 0.06 Y 2.91 Sc 0.2 Al 4.8 O 12 Fluorescence lifetime curve of the crystal;

[0021] Figure 5 Nd 0.03 Lu 0.06 Y 2.91 Sc 0.2 Al 4.8 O 12 The emission cross section of the crystal;

[0022] Figure 6 Nd 0.03 Lu 0.06 Y 2.91 Sc 0.2 Al 4.8 O 12 The relationship between the output power and output power of the crystal under output coupling mirrors with different transmittances. DETAILED DESCRIPTION

[0023] The invention provides a lutetium-scandium-neodymium co-doped yttrium-aluminum garnet crystal.

[0024] The present invention proposes that the chemical composition formula of the lutetium-scandium-neodymium co-doped yttrium aluminum garnet crystal is (Nd x Y 1-x-y Lu y )3(Al 1- z Sc z )2Al3O 12 , 0.002≤x≤0.013, 0.005≤y≤0.05, 0.1≤z≤0.2.

[0025] Lutetium and scandium are common elements in garnet structure, and the above doping amount is not enough to cause significant influence on the crystallization performance, quality of grown crystals and other optical, physical and chemical properties of Nd:YAG.

[0026] The preparation method of the lutetium-scandium-neodymium co-doped yttrium aluminum garnet crystal proposed in the present invention is mainly a melt method, including: Czochralski method, crucible descent method, horizontal directional crystallization method, guided mold method, etc., but not limited to the above methods. In order to obtain large-sized high-quality single crystals, the preferred preparation method is the Czochralski method.

[0027] The technical scheme and effects of the present invention are further described below in conjunction with embodiments and comparative examples.

[0028] Embodiment 1

[0029] Commercially available high-purity Y2O3, Nd2O3, Al2O3, Lu2O3 and Sc2O3 were selected as raw materials. 0.03 Lu 0.06 Y 2.91 Sc 0.2 Al 4.8 O 12 The raw materials were prepared, all the raw materials were mixed evenly, pressed into blocks, sintered at 1400℃ for 10h, and the single crystal was grown by the pulling method. The sintered cake was placed in an iridium crucible, and the crucible was heated to melt the raw materials. The pulling speed was 0.5mm / h, the rotation speed was 12r / min, and the growth atmosphere was inert gas. In order to compare the effect of lutetium-scandium doping on the effective segregation coefficient, luminescence characteristics, mechanical properties and thermal conductivity of the crystal, the same method and process parameters were used to grow Nd 0.03 Y 2.97 Al5O 12 3 grams of samples were taken from the heads of the two crystals near the seed crystals for testing Nd 3+ion concentration, and calculate the effective segregation coefficient; take a 10mm×10mm×2mm sample from each of the two crystal heads for spectrum, thermal conductivity, mechanical properties and laser efficiency testing. Test optical path as Figure 1 The test results are shown in Table 1. 0.03 Lu 0.06 Y 2.91 Sc 0.2 Al 4.8 O 12 The thermal conductivity test results are as follows: Figure 2 The mechanical properties tested are shown in Figure 3 As shown, the fluorescence lifetime tested is Figure 4 As shown, the emission cross section of the test is Figure 5 As shown, using Figure 1 The laser performance tested by the laser device shown is as follows Figure 6 shown.

[0030] Table 1 Nd 0.03 Lu 0.06 Y 2.91 Sc 0.2 Al 4.8 O 12 Comparison of performance parameters of crystal and Nd:YAG crystal

[0031] Crystal composition <![CDATA[Nd 0.03 AND 2.97 Al5O 12 ]]> <![CDATA[Nd 0.03 Sun 0.06 Y 2.91 Sc 0.2 Al 4.8 O 12 ]]> Effective fractionation coefficient 0.2 0.25 <![CDATA[Saturation Flux (J / cm 2 )]]> 0.66 1.2 Fluorescence lifetime (μs) 243 252 Thermal conductivity (W / mK) 10.5 10.5 Young's modulus(GPa) 289 284 Poisson's ratio 0.2576 0.2576 Vickers hardness (Hv) 1445 1437 <![CDATA[Fracture toughness (MPa / m 0.5 )]]> 1.26 1.21 Laser slope efficiency 0.68 0.63

[0032] Embodiment 2

[0033] Commercially available high-purity Y2O3, Nd2O3, Al2O3, Lu2O3 and Sc2O3 were selected as raw materials. 0.03 Lu 0.15 Y 2.82 Sc 0.3 Al 4.7 O 12 The raw materials were prepared, all the raw materials were mixed evenly, pressed into blocks, sintered at 1400℃ for 15h, and the single crystal was grown by the pulling method. The sintered cake was placed in an iridium crucible, and the crucible was heated to melt the raw materials. The pulling speed was 0.4mm / h, the rotation speed was 15r / min, and the growth atmosphere was inert gas. In order to compare the effect of lutetium-scandium doping on the effective segregation coefficient, luminescence characteristics, mechanical properties and thermal conductivity of the crystal, the same method and process parameters were used to grow Nd 0.03 Y 2.97 Al5O 12 3 grams of samples were taken from the heads of the two crystals near the seed crystals for testing Nd 3+ion concentration, and calculate the effective segregation coefficient; take a 5mm×5mm×2.5mm sample from each of the two crystal heads for spectrum, thermal conductivity, mechanical properties and laser efficiency testing. Test optical path as Figure 1 The test results are shown in Table 2.

[0034] Table 2 Nd 0.03 Lu 0.15 Y 2.82 Sc 0.3 Al 4.7 O 12 Comparison of performance parameters of crystal and Nd:YAG crystal

[0035]

[0036]

[0037] Embodiment 3

[0038] Commercially available high-purity Y2O3, Nd2O3, Al2O3, Lu2O3 and Sc2O3 were selected as raw materials. 0.006 Lu 0.015 Y 2.979 Sc 0.4 Al 4.6 O 12 The raw materials were prepared, all the raw materials were mixed evenly, pressed into blocks, sintered at 1440℃ for 13h, and the single crystal was grown by the pulling method. The sintered cake was placed in an iridium crucible, and the crucible was heated to melt the raw materials. The pulling speed was 0.35mm / h, the rotation speed was 6r / min, and the growth atmosphere was inert gas. In order to compare the effect of lutetium-scandium doping on the effective segregation coefficient, luminescence characteristics, mechanical properties and thermal conductivity of the crystal, the same method and process parameters were used to grow Nd 0.006 Y 2.994 Al5O 12 3 grams of samples were taken from the heads of the two crystals near the seed crystals for testing Nd 3+ ion concentration, and calculate the effective segregation coefficient; take a 5mm×5mm×2.5mm sample from each of the two crystal heads for spectrum, thermal conductivity and mechanical properties. The test results are shown in Table 3.

[0039] Table 3 Nd 0.006 Lu 0.015 Y 2.979 Sc 0.4 Al 4.6 O 12 Comparison of performance parameters of crystal and Nd:YAG crystal

[0040] Crystal composition <![CDATA[Nd 0.006 AND 2.994 Al5O 12 ]]> <![CDATA[Nd 0.006 Sun 0.015 Y 2.979 Sc 0.4 Al 4.6 O 12 ]]> Effective fractionation coefficient 0.2 0.22 <![CDATA[Saturation Flux (J / cm 2 )]]> 0.66 1.7 Fluorescence lifetime (μs) 251 253 Thermal conductivity (W / mK) 11.6 9.0 Young's modulus(GPa) 290 271 Poisson's ratio 0.2577 0.2534 Vickers hardness (Hv) 1441 1432 <![CDATA[Fracture toughness (MPa / m 0.5 )]]> 1.26 1.15

[0041] Embodiment 4

[0042] Commercially available high-purity Y2O3, Nd2O3, Al2O3, Lu2O3 and Sc2O3 were selected as raw materials. 0.039 Lu 0.015 Y 2.946 Sc 0.4 Al 4.6 O 12 The raw materials were prepared, all the raw materials were mixed evenly, pressed into blocks, sintered at 1400℃ for 15h, and the single crystal was grown by the pulling method. The sintered cake was placed in an iridium crucible, and the crucible was heated to melt the raw materials. The pulling speed was 0.3mm / h, the rotation speed was 5r / min, and the growth atmosphere was inert gas. In order to compare the effect of lutetium-scandium doping on the effective segregation coefficient, luminescence characteristics, mechanical properties and thermal conductivity of the crystal, the same method and process parameters were used to grow Nd 0.039 Y 2.961 Al5O 12 3 grams of samples were taken from the heads of the two crystals near the seed crystals for testing Nd 3+ ion concentration, and calculate the effective segregation coefficient; take a 5mm×5mm×2.5mm sample from the head of each of the two crystals for spectrum, thermal conductivity and mechanical properties. The test results are shown in Table 4.

[0043] Table 4 Nd 0.039 Lu 0.015 Y 2.946 Sc 0.4 Al 4.6 O 12 Comparison of performance parameters of crystal and Nd:YAG crystal

[0044] Crystal composition <![CDATA[Nd 0.039 AND 2.961 Al5O 12 ]]> <![CDATA[Nd 0.039 Sun 0.015 Y 2.946 Sc 0.4 Al 4.6 O 12 ]]> Effective fractionation coefficient 0.2 0.22 <![CDATA[Saturation Flux (J / cm 2 )]]> 0.66 1.7 Fluorescence lifetime (μs) 225 233 Thermal conductivity (W / mK) 10.1 8.5 Young's modulus(GPa) 290 271 Poisson's ratio 0.2575 0.2534 Vickers hardness (Hv) 1437 1435 <![CDATA[Fracture toughness (MPa / m 0.5 )]]> 1.25 1.13

Claims

1. A lutetium-scandium-neodymium co-doped yttrium-aluminum-garnet crystal, characterized in that: The chemical composition formula of the crystal is (Nd x Y 1-x-y Lu y )3(Al 1-z Sc z )2Al3O 12 , 0.002≤x≤0.013, 0.005≤y≤0.05, 0.1≤z≤0.

2.

2. The crystal growth method according to claim 1, characterized in that: The crystal is grown by a melt method.

3. The growth method according to claim 2, characterized in that: The melt method is a Czochralski method, a crucible descent method, a horizontal directional crystallization method or a guided mold method.

4. Use of the crystal according to claim 1 in a solid-state laser.

5. The use according to claim 4, characterized in that: Lasers are used in high-energy repetition rate lasers, laser shock strengthening, petawatt laser pump sources, laser fusion ignition devices or laser weapons.